HE4 as a biomarker for diagnosis of lung cancer: A meta-analysis. Issue 39 (September 2019) - He, Yong-Peng; Li, Li-Xian; Tang, Jia-Xi; Yi, Lin; Zhao, Yi; Zhang, Hai-Wei; Wu, Zhi-Juan; Lei, Hai-Ke; Yu, Hui-Qing; Nian, Wei-Qi; Gan, Lin
Abstract: Background: The aim of our study was to assess the value of serum human epididymis protein 4 (HE4) to diagnose lung cancer and provide reliable scientific conclusions to guide clinical practice. Methods: A systematic search of the PubMed, EMBASE, Cochrane Library, Chinese National Knowledge Infrastructure, Chinese Biomedical Literature, and WANFANG databases was conducted to identify all studies examining serum HE4 in the diagnosis of lung cancer published up to June, 2017. The Quality Assessment of Diagnostic Accuracy Studies tool was used to evaluate the methodological quality of each trial. The meta-analysis was performed using STATA software and Review Manager 5.3. Results: There were 21 studies involving 1883 cases and 1696 controls included in our meta-analysis. The pooled sensitivity and specificity of HE4 for diagnosing lung cancer were 0.73 (95% confidence interval [CI] 0.68–0.78) and 0.86 (95% CI 0.81–0.91), respectively. The positive likelihood ratio and negative likelihood ratio were 5.4 (95% CI 3.8–7.5) and 0.31 (95% CI 0.26–0.37), respectively. The diagnostic odds ratio was 17 (95% CI 12–26). The area under the curve of the summary receiver-operating characteristic curve was 0.86 (95% CI 0.83–0.89). Race, assay method, type of cancer, sample size, and publication date might be sources of heterogeneity in our meta-analysis. Subgroup analyses showed that the sensitivity in Caucasians was higher than that in Asians (0.81, 95% CI 0.71–0.91; and 0.71, 95% CI 0.66–0.77, respectively), but the specificity in Asians was better than that in Caucasians (0.87, 95% CI 0.81–0.92; and 0.85, 95% CI 0.73–0.97, respectively). The chemiluminescent microparticle immunoassay had the highest sensitivity, with 0.79 (95% CI 0.73–0.97), and the enzyme-linked immunosorbent assay had the highest specificity, with 0.87 (95% CI 0.79–0.94). HE4 had high diagnostic efficacy when screening for small cell lung cancer with the highest specificity (0.90, 95% CI 0.77–1.00). Conclusions: HE4 is a relatively promising and effective biomarker for the diagnosis of lung cancer. Furthermore, given the limitations of our study, additional large-scale and well-designed studies are needed in the future. Abstract : Supplemental Digital Content is available in the text